2011
DOI: 10.2320/matertrans.mb201018
|View full text |Cite
|
Sign up to set email alerts
|

EELS and <I>Ab-Initio</I> Study of Faceted CSL Boundary in Silicon

Abstract: Faceted AE3 CSL grain boundaries in silicon were investigated by high-resolution transmission electron microscopy (HRTEM), electron energy-loss spectroscopy (EELS) and ab-initio calculation. A {112} AE3 CSL boundary consisted of two segments which differed in atomic structure. The segment near the connected corner to {111} AE3 CSL boundary showed symmetric structure and the other long segment, being distant region from the corner, showed asymmetric structure. In the symmetric segment a 5-fold coordinated atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Moreover, a {111} 3 grain boundary, which is usually straight, is electrically inactive, but other CSL (coincidence site lattice) boundaries or random grain boundaries, which are straight, wavy or curved, are electrically active. Grain boundary structures are also investigated by transmission electron microscopy [52][53][54] or computer simulation [55][56][57]. Almost all studies of grain boundaries in Si have been performed after crystallization.…”
Section: Crystal-melt Interface At the Grain Boundary Formationmentioning
confidence: 99%
“…Moreover, a {111} 3 grain boundary, which is usually straight, is electrically inactive, but other CSL (coincidence site lattice) boundaries or random grain boundaries, which are straight, wavy or curved, are electrically active. Grain boundary structures are also investigated by transmission electron microscopy [52][53][54] or computer simulation [55][56][57]. Almost all studies of grain boundaries in Si have been performed after crystallization.…”
Section: Crystal-melt Interface At the Grain Boundary Formationmentioning
confidence: 99%
“…The presence of an undercoordinated O atom(s) relative to the bulk O atoms appear to play a key part in the formation of the prepeak, however the specific symmetry of the bonded O is likely also required to form the prepeak seen in the experimental EELS spectrum. Previous EELS experiments have shown that the formation of an O–K edge prepeak is influenced by the symmetry of the bonded atom(s). , Also, an analogous peak seen in transition metal spinels but not in MgAl 2 O 4 was interpreted as being from hybridization of O-p with metal p and d states, which further buttresses the emergence of this prepeak due to O bonded to Pt and Al at the interface.…”
Section: Resultsmentioning
confidence: 83%
“…Previous EELS experiments have shown that the formation of an O−K edge prepeak is influenced by the symmetry of the bonded atom(s). 71,72 Also, an analogous peak seen in transition metal spinels but not in MgAl 2 O 4 was interpreted as being from hybridization of O-p with metal p and d states, 73 which further buttresses the emergence of this prepeak due to O bonded to Pt and Al at the interface.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Some cases of such R3 grain boundaries consist of facets with {111} and {112} orientations, and the {112} facets introduce a lattice mismatch relaxed by an extended bond of a silicon atom with 5-fold-coordination. 13 Cases of macroscopically incoherent R3 grain boundary planes with a random plane orientation but microscopically coherent {111} and {112} facets with a neighboring array of dislocations were also found. 14 Small-angle grain boundaries (SAGBs), i.e., grain boundaries with their misorientation angle below 15 , can be also found in the material.…”
Section: Introductionmentioning
confidence: 90%